Capsid-Based Platform for Nano-Theranostic Reagent as Modularized Capsule: A Review - Chen, Chun-Chieh; Stark, Marie; Baikoghli, Mo A.; Cheng, R. Holland (Innovations in Microbiology and Biotechnology Vol. 6, 2022)
Hepatitis E Virus Nanoparticle (HEVNP), a modularized theranostics capsule produced from the HEV virus-like particle (VLP), has been presented as a multifunctional platform for cancer targeting, imaging, and therapeutic applications. This can be accomplished by using HEVNPs' flexible domain to attach various functional peptides and/or chemicals to the capsule surface while encapsulating medicines, DNA/RNA, or even inorganic beads inside the capsule's core. VLPs have advantages in terms of effective cell penetration via active endocytosis, polyvalence (the ability to anchor several copies of active substances), and biocompatibility (the ability to withstand proteolytic degradation after delivery). HEVNP's tumor targeting, and encapsulation capabilities could be used as a modularized theranostics nano-capsule in a variety of medical applications, including oral vaccines, cancer imaging, tumor-directed hyperthermia treatment, organ/tissue targeting gene therapy, and other therapeutics that lack targeting capability.